Praktik percaloan tiket film di Bioskop Surabaya tahun 1950-an - 1970-an - Arbaletta Kalinda Desvasivi Parameswari; Najib Jauhari; Grace Tjandra Leksana (Historiography: Journal of Indonesian History and Education, 2022)
This paper tries to describe to the reader the practice of brokering film tickets at the Surabaya cinema and how to handle it. The practice of ticket brokering itself is a crime that is affected by the existence of the cinema industry. The cinema industry emerged as a form of modernity in Surabaya in the field of entertainment for the community. The existence of this raises the question, how is the practice of brokering movie tickets in cinemas in Surabaya carried out? How is the public's response to this crime? How does the government deal with this brokering practice? By using historical research methods, this study examines a number of primary resources through archives. To find out how the practice of brokering film tickets is carried out in cinemas to the government's way of dealing with this brokering practice. The conclusions that can be drawn include: the practice of brokering film tickets in cinemas is carried out by unscrupulous persons to obtain profits that can be used to increase the needs of daily life. It is carried out with a neatly arranged modus operandi and has the support of several parties in the cinema. In response to this, the people were angry and filed complaints against the government, so anticipatory and repressive actions were carried out.Penulis mencoba menggambarkan kepada pembaca mengenai praktik percaloan tiket film di bioskop Surabaya dan cara menanganinya. Praktik percaloan tiket sendiri merupakan sebuah tindak kriminalitas yang terdampak dari adanya industri bioskop. Industri bioskop muncul sebagai bentuk adanya modernitas di Surabaya dalam bidang hiburan bagi masyarakat. Adanya hal tersebut memunculkan pertanyaan, bagaimanakah praktik percaloan tiket film dilakukan di bioskop-bioskop Surabaya?  Bagaimanakah respon masyarakat terhadap adanya kriminalitas ini? Serta bagaimanakah cara pemerintah menangani adanya praktik percaloan ini? Dengan menggunakan metode penelitian sejarah, studi ini menelusuri sejumlah sumber primer berupa arsip. Untuk mengetahui bagaimana praktik percaloan tiket film dilakukan di bioskop hingga cara pemerintah dalam mengatasi adanya praktik percaloan ini. Sehingga dapat diketahui bahwa praktik percaloan tiket film terjadi di bioskop dilakukan oleh oknum untuk mendapatkan keuntungan yang dapat digunakan untuk menambah kebutuhan hidup sehari-hari, dilakukan dengan modus operandi yang tersusun rapi serta mendapat dukungan dari beberapa pihak dalam bioskop. Merespon hal ini masyarakat marah dan mengajukan keluhan terhadap pemerintah, hingga dilakukan tindak antisipatif dan represif.